Aluminium Alloys Design and Development of Innovative Alloys, Manufacturing Processes and Applications - Timelli, Giulio (IntechOpen, 2022)
Aluminium alloys are among the most interesting materials being adopted for weight reduction and recycling benefits. The increasing importance of aluminium alloys over the years is due to their widespread use and applications in automotive, aerospace, food handling, building, heat exchange, and electrical transmission industries. Their high strength/weight ratio makes aluminium alloys useful for applications where simultaneous high strength and lightness are needed.This book provides a comprehensive review of the design and development of innovative aluminium alloys and composites. Chapters discuss manufacturing processes and applications and are heavily illustrated to make the concepts clear.